Wilder girls [large type] - Power, Rory (Thorndike Press, 2020)
It's been eighteen months since the Raxter School for Girls was put under quarantine. Since the Tox hit and pulled Hetty's life out from under her. It started slow. First the teachers died one by one. Then it began to infect the students, turning their bodies strange and foreign. Now, cut off from the rest of the world and left to fend for themselves on their island home, the girls don't dare wander outside the school's fence, where the Tox has made the woods wild and dangerous. They wait for the cure they were promised as the Tox seeps into everything. But when Byatt goes missing, Hetty will do anything to find her, even if it means breaking quarantine and braving the horrors that lie beyond the fence. And when she does, Hetty learns that there's more to their story, to their life at Raxter, than she could have ever thought true.